Maternal Mortality in East Lombok: Recent Trends, Clinical Concerns, and Future Recommendations - Prabawati, Novya; Sucipta, Dewa Made; Prabawati, Nurul Hidayati; Rahman, Maizar (Balai Publikasi Indonesia, 2025)
The worldwide maternal mortality ratio (MMR) should be below 70 deaths per 100,000 live births in 2030. In the context of Indonesia, the MMR (189) and West Nusa Tenggara Province exceeds the national MMR to 257. MMR of East Lombok Regency was 118.5 deaths per 100,000 live births at 2024, it requires the recent trends in regency level, find the clinical cause and propose the future recommendations. Based on the trend in the last 2020-2024, East Lombok Regency experienced fluctuation rate. Based on the data from Department of Health of East Lombok Regency, the clinical causes of maternal mortality ratio from 2020 to 2024 are hemorrhage, infection, hypertension in pregnancy, cardiovascular disorder, metabolic disorder, covid-19, and others. Several recommendations to be considered are improving emergency response & referral systems, improving emergency response & referral systems, addressing socioeconomic and cultural barriers, and strengthening data monitoring and policy implementation